Post-lockdown SARS-CoV-2 nucleic acid screening in nearly ten million residents of Wuhan, China - Shiyi Cao (Nature Portfolio, 2020)
Large-scale population screening can provide insights to levels of ongoing SARS-CoV-2 transmission. Here, the authors report a citywide screening of ~10,000,000 residents of Wuhan and show that SARS-CoV-2 infection prevalence was very low five to eight weeks after the end of lockdown.